Challenging El Salvador's Rural Health Care Strategy - Eskeland, Gunnar S. 1959- (The World Bank, 1999)
August 1999 - Low-skilled health promoters posted in rural villages are doing little to improve health or health-seeking behaviors. In a supply-driven system, such workers have too few incentives, too little knowledge, and too little supervision. Results can be improved without increasing costs. Can a supply-driven network of under-skilled rural health promoters make a difference in rural health care? There are few, if any, signs that the current rural health strategy in El Salvador is working, whether the health promoters are government employees or nongovernmental organization (NGO) workers. Lewis, Eskeland, and Traa-Valerezo arrived at this conclusion after conducting interviews and analyzing primary and secondary data. The village-based health promoters lack incentives and supervision, and ultimately have little to offer local communities. NGO workers are more successful than government workers, but neither group performs satisfactorily. Even the rural poor use private services quite intensively, despite the high cost of the services and of getting access to them. Moreover, people seem to seek the services they need. They select self-treatment in 50 percent of illness episodes, with about the same success rate as when they use health providers. Other options should be considered, as results can be improved without increasing costs. This paper - a product of the Human Development Sector Units, Europe and Central Asia Region and Latin America and Caribbean Region; and Public Economics, Development Research Group - is part of a larger effort in the Bank to encourage appropriate policies and programs in the health sector. The authors may be contacted at mlewis1@worldbank.org, geskeland@worldbank.org, or xtraavalerezo@worldbank.org